Sero-prevalences of Tick-borne infections among the Nkedi Zebu and Ankole cattle in Soroti district, Uganda - Kabi, F.; Magona, J.W.; Nasinyama, G.W.; Walubengo, J. (The Journal of Protozoology Research, 2008)
This cross-sectional study was conducted to establish and compare the antibody titres and sero-prevalences of tick-borne infections among randomly selected Nkedi Zebu and Ankole cattle in the six villages of Akumoi, Aswii, Kamod, Osamito, Okokoma and Opungure in Soroti district, Uganda. The antibody titres were established using the indirect antibody detection ELISA tests. The Nkedi Zebu had a significantly higher mean antibody titre against T. parva infection (1.8 ± 0.1) compared to the Ankole cattle (1.2 ± 0.1). While the mean antibodies titres of Ankole against B. bigemina and A. marginale infections (2.2 ± 0.04, 0.05 ± 0.05) respectively were very similar to those of the Nkedi Zebu cattle (2.1 ± 0.05, 0.06 ± 0.05) respectively. Sero-prevalences of East Coast Fever, babesiosis and anaplasmosis (100%, 100%, 58%) among the Ankole cattle were quite similar to those of Nkedi Zebu cattle (99%, 100%, 57%) respectively. This study has demonstrated that the Nkedi Zebu are better primed to produce antibodies against T. parva as compared to the Ankole cattle, thus extra control strategies for tick-borne infections need to be instituted if the Ankole cattle are to be reared successfully in this agro-pastoral farming system.
Keywords: Agro-pastoral; Antibody titres; Sero-prevalence; Tick-borne infections